2013
DOI: 10.1108/09600031311293255
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the causes for retail stockouts

Abstract: PurposeThe purpose of this paper is to increase our understanding of the causes for stockouts in retailing.Design/methodology/approachMixed methods study, using instore observations, interviews with key informants in consumer goods and retailing, and a field study of stockouts and their causes in multiple wholesale stores over two years.FindingsThe results indicate that the causes for stockouts are specific to retailer, store, category and item. Improvements to store operations and the coordination of store de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 41 publications
0
57
0
Order By: Relevance
“…The identified processes are independent from the store format and include activities and processes dedicated to making products available at the point of sale and giving them the best chance of being sold (see Process 2: "Instore logistics"; Kotzab and Teller, 2005;van Donselaar et al, 2006;Reiner et al, 2013). From our interviews we found that the inherent, paramount aim behind those processes is to provide sufficient onshelf availability and reduce the opportunity costs related to out-of-stock situations (Ehrenthal and Stölzle, 2013). In most cases products are sold (see Decision 3: "Product sold?")…”
Section: From Delivery To the Selling Of The Productsmentioning
confidence: 98%
See 1 more Smart Citation
“…The identified processes are independent from the store format and include activities and processes dedicated to making products available at the point of sale and giving them the best chance of being sold (see Process 2: "Instore logistics"; Kotzab and Teller, 2005;van Donselaar et al, 2006;Reiner et al, 2013). From our interviews we found that the inherent, paramount aim behind those processes is to provide sufficient onshelf availability and reduce the opportunity costs related to out-of-stock situations (Ehrenthal and Stölzle, 2013). In most cases products are sold (see Decision 3: "Product sold?")…”
Section: From Delivery To the Selling Of The Productsmentioning
confidence: 98%
“…Corsten and Gruen, 2003;Ehrenthal and Stölzle, 2013). Other authors focus on store replenishment and the efficiency of store operations processes (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Attention has been devoted to its measuring (Roland Berger Consultants, 2003;Gruen, Corsten, 2007), identifying (Papakiriakopoulos et al, 2009;Papakiriakopoulos, Doukidis, 2011) main root causes (Fernie, Grant, 2008;Ehrenthal, Stolzle, 2013), effects (Gruen, 2007;Musalem et al, 2010), and customer responses in out-of-stock situations (van Woensel et al, 2007;Zinn, Liu, 2008).…”
Section: Retail Product Availabilitymentioning
confidence: 99%
“…Higher inventory holding costs, inaccurate information exchange and sales planning are just some of them. However, to retailers, one of the biggest issues is related to a decrease in store loyalty (Ehrenthal & Stolzle, 2013), which can have long term consequences on business performance. Even though the consumer switching rate is still undocumented, the annual cost of permanent shopper loss to competitors is estimated at US $1 million per every 200 shoppers (Gruen & Corsten, 2007).…”
Section: Introductionmentioning
confidence: 99%